Clinical effectiveness and cost-effectiveness of foot orthoses for people with established rheumatoid arthritis: an exploratory clinical trial. (4th May 2017) - Rome, K; Clark, H; Gray, J; McMeekin, P; Plant, M; Dixon, J
Abstract : Objectives : Foot orthoses are commonly prescribed as an intervention for people with rheumatoid arthritis (RA). Data relating to the cost-effectiveness of foot orthoses in people with RA are limited. The aim was to evaluate the clinical and cost-effectiveness of two types of foot orthoses in people with established RA. Method : A single-blind randomized controlled trial was undertaken to compare custom-made foot orthoses (CMFOs) and simple insoles (SIs) in 41 people with established RA. The Foot Function Index (FFI) was used to measure foot pain, disability, and functional limitation. Costs were estimated from the perspective of the UK National Health Service (NHS), societal (patient and family) perspective, and secondary care resource use in terms of the intervention and staff time. Effects were assessed in terms of health gain expressed as quality-adjusted life years (QALYs). Results : At baseline, 20 participants received a CMFO and 21 participants received an SI. After 16 weeks foot pain improved in both the CMFOs (p = 0.000) and the SIs (p < 0.01). However, disability scores improved for CMFOs (p < 0.001) but not for SIs (p = 0.40). The cost-effectiveness results demonstrated no difference in cost between the arms (CMFOs: £159.10; SIs: £79.10; p = 0.35), with the CMFOs being less effective in terms of cost per QALY gain (p < 0.001). Conclusions : In people with established RA, semi-rigid customized foot orthoses can improve pain and disability scores in comparison to simple insoles. From a cost-effectiveness perspective, the customized foot orthoses were far more expensive to manufacture, with no significant cost per QALY gain.